2015
DOI: 10.1111/omi.12124
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal and peri‐implant diseases: identical or fraternal infections?

Abstract: Peri-implant diseases (peri-implantitis and peri-implant mucositis) are bacterially driven infections. Peri-implantitis leads to aggressive bone resorption and eventual loss of the implant. Traditionally, peri-implantitis was regarded as microbially similar to periodontitis, and translocation of periodontal pathogens into the peri-implant crevice was considered as a critical factor in disease causation. However, evidence is emerging to suggest that the peri-implant and periodontal ecosystems differ in many imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 98 publications
0
55
0
3
Order By: Relevance
“…Although peri‐implantitis and periodontitis have many features in common in clinical and radiologic signs, they represent distinct entities because of their different anatomic and histologic environments, core microbiomes and immune characteristics . Peri‐implantitis displays unique features and the destruction of tissues in peri‐implantitis appears to be of significantly greater severity than occurs in periodontitis .…”
Section: Introductionmentioning
confidence: 99%
“…Although peri‐implantitis and periodontitis have many features in common in clinical and radiologic signs, they represent distinct entities because of their different anatomic and histologic environments, core microbiomes and immune characteristics . Peri‐implantitis displays unique features and the destruction of tissues in peri‐implantitis appears to be of significantly greater severity than occurs in periodontitis .…”
Section: Introductionmentioning
confidence: 99%
“…Prior publications have associated gram negative bacteria with periodontal disease as well as peri‐implantitis . Recent metagenomics studies, however, have identified distinctive microbial signatures of the peri‐implant and periodontal biofilms . Nevertheless, some of the bacteria found around implants with peri‐implantitis have been similar species to those found around teeth that are diagnosed with chronic periodontitis .…”
Section: Discussionmentioning
confidence: 99%
“…4,45,46 Recent metagenomics studies, however, have identified distinctive microbial signatures of the peri-implant and periodontal biofilms. 6,47 Nevertheless, some of the bacteria found around implants with peri-implantitis have been similar species to those found around teeth that are diagnosed with chronic periodontitis. 18,43,48 It is not clear if the bacteria occupy the peri-implant niche by proximity or whether they are associated with the etiology of peri-implant disease.…”
Section: Interpretation Of the Study Supported By Existing Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…3 Removal of bacteria can resolve the soft-tissue inflammation, but, once the lesion invades bone, reversal capabilities are lost. 4 Preventive measures aiming primarily at discouraging biofilm formation have been proposed following various approaches. 5 Some of the most studied methods comprise finishing implant material surfaces with repellent coatings, antimicrobials, surfactants and hydroxyapatites.…”
Section: Introductionmentioning
confidence: 99%